Exploring user experiences of the National Institute of Health and Care Excellence’s Shared Decision Making learning package: an online qualitative study - Jonathan Underhill; Neal Maskrey; Simon Jacklin; Jessica Thompson; Andy Hutchinson; Katie Maddock; Laura Norburn (BMJ Open)
Objective To evaluate the user experience of the joint National Institute of Health and Care Excellence (NICE)/Keele University Shared Decision Making (SDM) learning package.Design A qualitative study using online semistructured interviews. Data were analysed using open coding followed by the construction of themes.Setting Participants were recruited and interviewed online via Microsoft Teams.Participants Healthcare professionals who had used the NICE SDM learning package and provided contact details between June 2021 and April 2022 were eligible to be contacted.Intervention The online learning package developed to support the implementation of the NICE SDM guideline.Findings 12 participants from a variety of different professional backgrounds were interviewed and reported that the learning package was easy to use and the different formats for presenting the information were engaging. The package was available in discrete sections—‘bitesize’ chunks—which allowed the participants to fit their learning around their busy schedules. The package included virtual patients (VPs) which allowed users to practice their SDM skills and put the learning into practice. The VPs also stimulated reflection on current performance and a shift in approach to SDM in practice. Suggestions were made by participants to improve the usability and accessibility of the learning package.Conclusion The NICE SDM learning package was viewed favourably by the participants. The bitesize structure and interactivity were key positive elements. Many participants suggested that they had made changes to their practice as a result of using the package.